2017
DOI: 10.1039/c6ta11127k
|View full text |Cite
|
Sign up to set email alerts
|

High-performance urea electrolysis towards less energy-intensive electrochemical hydrogen production using a bifunctional catalyst electrode

Abstract: Ni2P nanoflake arrays on carbon cloth act as an efficient and durable catalyst electrode for the urea oxidation reaction (UOR) and hydrogen evolution reaction (HER). Its two-electrode alkaline electrolyzer needs 1.35 V for 50 mA cm−2, which is 0.58 V less than that required for pure water splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
179
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 315 publications
(182 citation statements)
references
References 65 publications
3
179
0
Order By: Relevance
“…Table 2 summarises the results of UOR parameters of catalysts. [24,25,27,29] Notably, onset potential Ni MOF for UOR was found to be at 1.34 V vs. RHE; which was closer to recent reports of NiFe LDH and Ni NP by Gao et al, b Ni(OH) 2 and Ni/Ni(OH) 2 by Singh et al, MOF-Templated Ni/C by Wang et al and higher than that of Ni MOF (BDC) by Zhu et al [27,30,42,43] On the other hand, high catalytic current density (63.15 mA cm À2 at 1.5 V vs. RHE) of Ni MOF compared to NiO WCP (8.32 mA cm À2 at 1.5 V vs. RHE) and NiO SA (30.47 mA cm À2 at 1.5 V vs. RHE) in the UOR indicates the high catalytic activity of Ni MOF towards UOR and it is found to be similar to OER catalytic activity of the present study. Meanwhile, in the presence of urea, catalytic current rose around 1.3 V vs. RHE as a result of UOR by Ni(OH) 2 /NiOOH redox, which was similar to OER and the previous reports.…”
Section: Urea Electrolysismentioning
confidence: 99%
See 3 more Smart Citations
“…Table 2 summarises the results of UOR parameters of catalysts. [24,25,27,29] Notably, onset potential Ni MOF for UOR was found to be at 1.34 V vs. RHE; which was closer to recent reports of NiFe LDH and Ni NP by Gao et al, b Ni(OH) 2 and Ni/Ni(OH) 2 by Singh et al, MOF-Templated Ni/C by Wang et al and higher than that of Ni MOF (BDC) by Zhu et al [27,30,42,43] On the other hand, high catalytic current density (63.15 mA cm À2 at 1.5 V vs. RHE) of Ni MOF compared to NiO WCP (8.32 mA cm À2 at 1.5 V vs. RHE) and NiO SA (30.47 mA cm À2 at 1.5 V vs. RHE) in the UOR indicates the high catalytic activity of Ni MOF towards UOR and it is found to be similar to OER catalytic activity of the present study. Meanwhile, in the presence of urea, catalytic current rose around 1.3 V vs. RHE as a result of UOR by Ni(OH) 2 /NiOOH redox, which was similar to OER and the previous reports.…”
Section: Urea Electrolysismentioning
confidence: 99%
“…[15,20] Methanol, ammonia and urea offer an easy way to store hydrogen as a low cost chemical in industrial scale as well as urea is found in fertilizers and municipal waste water from human/animal urine. [22][23][24][25]28] Similar to OER in WE, Ni based catalysts such as nano sized nickel, LaNiO 3 , NiÀFe double hydroxide, Ni 2 P, Ni(OH) 2 , Ni nanoparticles decorated NiFe double hydroxide, Ni x Mn y O 4 show catalytic activity towards UOR. [23][24][25][26][27] Because of its lower energy consumption, wider availability, renewability, non-flammability and non-toxic nature, UE enables H 2 production from the urea rich waste water and animals excreta.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…One of them is to modify Ni with nitrogen group or oxygen group elements, in order to modify the catalytic preference of the catalysts for bifunctional activity in UOR and HER. For example, Liu et al reported the fabrication of carbon cloth with Ni 2 P nanoflake arrays (Ni 2 P NF/CC), where its morphology and elemental distribution are shown in Figure a,b . The catalyst is prepared by means of hydrothermal reactions with nickel nitrate hexahydrate (Ni(NO 3 ) 2 ·6H 2 O) and hexamethylenetetramine, followed by the phosphorization process by the thermal decomposition of sodium hypophosphite (NaH 2 PO 2 ).…”
Section: Urea Electrolysis For Hydrogen Productionmentioning
confidence: 99%